PENGARUH PERLAKUAN FERMENTASI DAN AMONIASI KULIT SINGKONG TERHADAP NILAI KECERNAAN BAHAN KERING DAN BAHAN ORGANIK RANSUM PADA DOMBA JANTAN - Agung Dwi Nugroho; Muhtarudin Muhtarudin; Erwanto Erwanto; Farida Fathul (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
This research aimed to determine the effect of fermentation and ammoniation treatment of cassava peels on ration on dry matter digestibility (DMD) and organic matter digestibility (OMD) in male sheeps. This research was conducted in May–June 2019 in the cage unit and the Laboratory of Nutrition and Animal Feed, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The experimental design applied was a completely randomized design (CRD) with 3 treatments and 3 replications. The experimental unit used were 9 sheeps. The treatments given were ration+15% cassava peels without treatment (R0), ration+15% fermented cassava peels (R1), and ration+15% ammoniated cassava peels (R2). The results showed that the use of cassava peel fermentation and ammoniation treatment had a significant effect (P<0.05) on dry matter digestibility (DMD) and organic matter digestibility in male sheep. The average of total digestibility of dry matter and organic matter of ration showed an increase of digestibility. The treatment of fermentation and ammoniation gave the best effect when compared to that without processing. Keywords: Ammoniation, Fermentation, Cassava peels, Dry matter digestibility and organic matter digesbility, Sheep